Initial growth of coffee plants (Coffea arabica L.) submitted to different phosphate doses in nutritive solution - Matsumoto, Sylvana Naomi; Carvalho, Fábio Martins de; Viana, Anselmo Eloy Silveira; Malta, Marcelo Ribeiro; Castro, Luciana Gomes (Coffee Science - ISSN 1984-3909)
The objective of this study was to evaluate growth alterations and water relations in coffee plants (Coffea arabica L.) at the initial stage of development, grown in nutritive solution (hydroponics) and submitted to a wide variation of P doses. The various doses of P applied to the coffee plants similarly affected the growth characteristics evaluated (number of leaves, height, total leaf area, and dry and green mass accumulation), fitting a logarithmic model, with a direct relationship between P doses and growth. The logarithmic model was also fitted to the leaf water potential module, evaluated in the pre-dawn period and at noon. However, the direct relationship between P doses and water potential was only verified for determinations made at noon; the opposite behavior occurred with readings made in the pre-dawn period, since values decreased as P doses increased. Interactions between P and N nutritional status as well as between P and the water status of plants are discussed, with emphasis on the importance of future investigations.